2013
DOI: 10.24135/afl.v2i1.9
|View full text |Cite
|
Sign up to set email alerts
|

What Behavioural Economics Has to Say about Financial Literacy

Abstract: Gaps in financial literacy are arguably responsible for significant errors in decision-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…There is ample evidence that many individuals make suboptimal decisions when it comes to financial decision-making such as investment, credit card use and pension decisions, which can have strong implications for society as a whole (Agarwal and Mazumder, 2013;Altman, 2013). One possible reason for this is that individuals are boundedly rational (Simon, 1959), as information acquisition is costly and individuals' capacity to process complex information is limited.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is ample evidence that many individuals make suboptimal decisions when it comes to financial decision-making such as investment, credit card use and pension decisions, which can have strong implications for society as a whole (Agarwal and Mazumder, 2013;Altman, 2013). One possible reason for this is that individuals are boundedly rational (Simon, 1959), as information acquisition is costly and individuals' capacity to process complex information is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of knowledge and cognitive abilities for optimal decision-making in many domains, the design of the decision-making environment should receive greater attention by researchers and policy makers (Altman, 2012(Altman, , 2013. It has been demonstrated that setting up education programs and providing high-quality decision aids in the decision situation can empower consumers to make better financial decisions (Bernheim et al, 2001;Goda et al, 2014;Savikhin, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y Herded,t|PI=1 = 0 + β 1 Warning t + β 2 PI 30− 49% + β 3 PI 50− 69% + β 4 PI 70− 89% + β 5 Retirement + β 6 X + ε t (3) covariates in specifications used for the logit analyses. 2 In Panel B of Table 1, we present the share of respondents choosing each of the three options.…”
Section: Dssmentioning
confidence: 99%
“…Behavioural decision theory, which analyses why and how decisions are made [6], has shown that humans tend to "imitate each other's actions and/or base their decisions upon the actions of others" ( [51], p. 175). Individuals herd when they believe that the 'crowd' is better informed than they are [3,8,10,13], or because of an intrinsic preference for conformity [22,33]. It has been argued that insights from behavioural economics should be integrated more intensively in decision support systems (DSS) research [6,36].…”
Section: Introductionmentioning
confidence: 99%